2019
DOI: 10.1016/j.jcis.2018.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic surface patterns from Bénard‐Marangoni instabilities upon evaporation of a reactive ZnO nanofluid droplet: A fractal dimension analysis

Abstract: We present a box counting fractal dimension (FD) analysis of the dendritic patterns obtained under conditions far from equilibrium via rapid evaporation of a sessile drop containing reactive ZnO nanoparticles. These dendrites were manifestations of solidified Bénard-Marangoni (BM) instability convection cells, and we previously noted that their complex hierarchical morphologies were superficially analogous to the foliage of red algae, Spanish dagger, or spider plant. The fractal dimension of the Bénard-Marango… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…We attributed this discrepancy to the different deposition method used in that study, i.e. drop casting of isopropanol solution containing 0.01 wt% erucamide, with the driving forces for the layer formation likely dominated by the capillary flow and surface tension upon evaporation of the sessile drop [52][53][54][55]. The geometric packing of erucamide molecules in its self-assembled structures can be considered via the packing parameter P = 𝑉 𝑎 0 𝐿 𝑚𝑎𝑥 [56], where 𝐿 𝑚𝑎𝑥 = 1.5 + 1.265𝑛 𝐶 is the maximum length of a fully extended hydrocarbon chain of nc carbon atoms [48].…”
Section: Nanofilm Structure At Lower Erucamide Concentrationsmentioning
confidence: 95%
“…We attributed this discrepancy to the different deposition method used in that study, i.e. drop casting of isopropanol solution containing 0.01 wt% erucamide, with the driving forces for the layer formation likely dominated by the capillary flow and surface tension upon evaporation of the sessile drop [52][53][54][55]. The geometric packing of erucamide molecules in its self-assembled structures can be considered via the packing parameter P = 𝑉 𝑎 0 𝐿 𝑚𝑎𝑥 [56], where 𝐿 𝑚𝑎𝑥 = 1.5 + 1.265𝑛 𝐶 is the maximum length of a fully extended hydrocarbon chain of nc carbon atoms [48].…”
Section: Nanofilm Structure At Lower Erucamide Concentrationsmentioning
confidence: 95%
“…6), consisting of dendritic feather-like aggregates of some μm in length scale with no particular alignment. The dendritic fractal 68,69 morphology (seen in detail in Fig. 6c, d) exhibits a central fibre that supports secondary fibres, which in turn support tertiary fibres, and so on.…”
Section: Microscopic Structure Of the Ordered Surfactant Mesophasementioning
confidence: 99%
“…We found that the dimensions of the solidified Beńard cells depended on the substrate used due to different BM flows on these substrates. To go beyond a descriptive account of the surface pattern, the quasi-two-dimensional BM convection cells were analyzed using the box counting fractal dimension (FD) analysis 27 that provided a quantitative description of the BM cells with complex structural hierarchy, highlighting the differences in the geometric features of the surface patterns resulting from different substrate chemistry. We show that the surface chemistry of the substrate influences the dimension of the solidified BM cells during the ZnO nano/ microfluid evaporation, and we discuss this effect in terms of the substrate−water interactions, as water is crucial to the ZnO nanocrystal dissolution in the pattern formation mechanism from such reactive nanofluids.…”
Section: ■ Introductionmentioning
confidence: 99%